Inositol supplementation - known and possible applications - Swora, Aleksandra; Borowik, Joanna; Brodowski, Wojciech; Sygacz, Oliwer; Pawłowski, Piotr; Żelazny, Przemysław; Filipczak, Joanna; Dankiewicz, Sara; Bróż, Sebastian; Basta-Arciszewska, Katarzyna (Journal of Education, Health and Sport, 2022)
Introduction: Myo-inositol (MYO) and D-chiro-inositol are chemical compounds known to exert an impact on multiple signaling pathways of a human body. Due to its effects on insulin metabolism and ovaries’ hormone activity their use in polycystic ovary syndrome (PCOS) therapies has been highly recommended in the recent literature. In this article we aim to review the known and possible applications of inositol and its derivatives for treatment of various gynecological and endocrine disorders and to indicate possible directions of further investigations. Methods and materials: This article is based on the literature found in PubMed Database from the period of 2016-2022 with use of keywords such as “inositol”; “myoinositol”; “d-chiro-inositol”; “PCOS”; “insulin”. Results: The applications of myoinositol in the treatment of polycystic ovary syndrome (PCOS) are very well known in recent publications. It is reported that MYO supplementation improves the quality of oocytes, regulates the menstrual cycle and ovulation rates. Prevention of gestational diabetes (GDM) amongst the patients with risk factors is likely another use of inositols. Inositol takes part in phospholipase C pathway, thus its depletion may be the cause for hypothyroidism. Inositol inhibits the expression of aromatase, the enzyme which is responsible for the growth of endometrial tissue - it may constitute a targeting point in the treatment of endometriosis. So far, no adverse effects of inositol isomers have been reported. Conclusion: The use of inositol, its isomers and derivatives represents an interesting direction in the development of the treatment of many conditions associated with endocrine disorders. There is a need for further investigations and studies on larger groups of patients to exploit its potential.